Diversity of the Bacterial Microbiome Associated With the Endosphere and Rhizosphere of Different Cassava (Manihot esculenta Crantz) Genotypes - Ha, Jingwen; Gao, Yu; Zhang, Rui; Li, Ke; Zhang, Yijie; Niu, Xiaolei; Chen, Xin; Luo, Kai; Chen, Yinhua (Frontiers in Microbiology, 2021)
Root-associated microbial communities play important roles in plant growth and development. However, little attention has been paid to the microbial community structures associated with cassava, which is a staple food for approximately 800 million people worldwide. Here, we studied the diversity and structure of tuber endosphere and rhizosphere bacterial communities in fourteen cassava genotypes: SC5, SC8, SC9, SC205, KU50, R72, XL1, FX01, SC16, 4612, 587, 045, S0061, and 1110. The results of bacterial 16S rDNA sequencing showed that the richness and diversity of bacteria in the rhizosphere were higher than those in the tuber endosphere across the fourteen cassava genotypes. After sequencing, 21 phyla and 310 genera were identified in the tuberous roots, and 36 phyla and 906 genera were identified in the rhizosphere soils. The dominant phylum across all tuber samples was Firmicutes, and the dominant phyla across all rhizosphere samples were Actinobacteria, Proteobacteria, and Acidobacteria. The numbers of core bacterial taxa within the tuber endospheres and the rhizospheres of all cassava genotypes were 11 and 236, respectively. Principal coordinate analysis and hierarchical cluster analysis demonstrated significant differences in the compositions of rhizosphere soil microbiota associated with the different cassava genotypes. Furthermore, we investigated the metabolic changes in tuber roots of three genotypes, KU50, SC205 and SC9. The result showed that the abundances of Firmicutes, Proteobacteria, and Actinobacteria in tuber samples were positively correlated with organic acids and lipids and negatively correlated with vitamins and cofactors. These results strongly indicate that there are clear differences in the structure and diversity of the bacterial communities associated with different cassava genotypes.